2009
DOI: 10.1111/j.1365-2044.2009.06105.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the laryngeal mask airway with the facemask and oropharyngeal airway for manual ventilation by first responders in children

Abstract: In adults, first responders to a cardiopulmonary arrest provide better ventilation using a laryngeal mask airway than a facemask. It is unclear if the same is true in children. We investigated this by comparing the ability of 36 paediatric ward nurses to ventilate the lungs of 99 anaesthetised children (a model for cardiopulmonary arrest) using a laryngeal mask airway and using a facemask with an oropharyngeal airway. Anteroposterior chest wall displacement was measured using an ultrasonic detector. Nurses ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In 2 LOE 5 studies of anesthetized children 145,146 suitably trained ICU and ward nurses placed LMAs with a high success rate, although time to first breath was shorter in the BMV group. In a small number of cases ventilation was achieved with an LMA when it proved impossible with BMV.…”
Section: Airway and Ventilationmentioning
confidence: 99%
“…In 2 LOE 5 studies of anesthetized children 145,146 suitably trained ICU and ward nurses placed LMAs with a high success rate, although time to first breath was shorter in the BMV group. In a small number of cases ventilation was achieved with an LMA when it proved impossible with BMV.…”
Section: Airway and Ventilationmentioning
confidence: 99%
“…Cook et al reported that the most frequent reason for suboptimal ventilation with the LMA was an imperfect seal 16. Because successful insertion of the LMA varied by professional group in the present study, the optimal insertion in our study of the LMA seems to be experience-dependent; however, there are two relevant studies by Rechner et al and Blevin et al that showed good success rates for the use of the LMA by inexperienced healthcare workers in children when the LMA and facemask ventilation were compared 11 12. Furthermore, the variability of the success rate in the use of the LMA in our groups could be explained by the different techniques for LMA insertion which were not limited in the present study 8 9…”
Section: Discussionmentioning
confidence: 60%
“…However, it must be noted that the first-line method of attaining airway control in children is bag-mask ventilation because successful airway management in children requires a high level of skill and regular training 1 11 12. Nevertheless, SADs, such as the LMA, LTS and I-gel, are recognised as possible alternatives to achieve airway control in a paediatric emergency.…”
Section: Discussionmentioning
confidence: 99%
“…(41) In the prehospital environment, based on the limited paediatric literature available, bag-valve-mask should be used for initial airway management. However, if there are issues ventilating a critically ill or collapsed paediatric patient, it is reasonable to use appropriate supraglottic devices, especially laryngeal masks, as a rescue device in conjunction with bag-valve-mask.…”
Section: Laryngeal Mask Airway and Supraglottic Devicesmentioning
confidence: 99%